Phamacognostical Evaluation and Determination of Total Phenols of Paeonia sinjiangensis K. Y. Pan - H. Y. Gong; X. M. Ma; S. G. Tian (E-Journal of Chemistry)
Paeonia sinjiangensis K. Y. Pan is a perennial herb belonging to the family Ranunculaceae which is one of the most important crude drugs in traditional Chinese medicine, used as an anti-inflammatory, analgesic and sedative agent. This paper deals with the detailed pharmacognostical evaluation of the crude drug P. sinjiangensis K. Y. Pan. The microscopic, physico-chemical, preliminary physicochemical parameters, total phenols contents presented in this paper may be proposed as parameters to establish the authenticity of P. sinjiangensis K. Y. Pan and can possibly help to differentiate the drug from its other species.